Editorial. Issue 1 (1st July 2022) - McCarthy, Conal; Brown, Alison K.
Abstract : Museum studies is an academic and practical field of research that is ever expanding and alive with potential, opportunity, and challenge paralleling the extraordinary growth of museums in every part of the world. Museum Worlds: Advances in Research, launched in 2012, has responded to the need for a rigorous, in-depth review of current work in museums and related industries, including galleries, libraries, archives, and cultural heritage. The inspiration for the journal came from Howard Morphy, Professor of Anthropology at the Australian National University in Canberra, along with founding editors Kylie Message, also at the ANU, and Sandra Dudley from the School of Museum Studies at the University of Leicester.